Friction stabilities of gypsum and kaolinite/calcite mixture fault gauges under high pressure - Dongsheng Ren (Frontiers in Earth Science, 2024)
Various lab-scale friction tests and seismic observations have highlighted the role of fault gauges in earthquake initiation in geological faults. These fault gauges consist of particles accumulated over thousands of years due to surface wear caused by friction. Understanding their properties is crucial as they significantly influence both the frictional strength and sliding stability of faults. This study investigates the friction stability parameter (a-b) under loading rates of 0.2–25 μm/s using velocity step tests on gypsum fault gauges under a low normal stress condition (0.9 MPa) and steady-state velocity step tests on fault gauges composed of varying ratios of kaolinite/calcite mixture under an effective normal stress of 3 MPa. The conclusions drawn from this study are as follows: 1) The (a-b) values obtained from near steady-state velocity step tests on gypsum fault gauges and those reported in previous studies under similar conditions were both negative. However, our results show that the former values were one order of magnitude lower than the latter, indicating a higher susceptibility to velocity weakening. 2) Steady-statevelocity steptests on the kaolinite/calcite mixture fault gauges demonstrated positive (a-b) values for all mixtures with varying kaolinite contents. Moreover, the (a-b) values were proportional to the kaolinite content. We established a functional relationship between the (a-b) values of the mixture fault gauge and the mass fraction of kaolinite, providing valuable insights for future experiments and numerical simulations related to fault stability.